States of imitation: mimetic governmentality and colonial rule - Ladwig, Patrice; Roque, Ricardo (Studies in social analysis, 2020)
Introduction: Mimetic governmentality, colonialism, and the state / Patrice Ladwig and Ricardo Roque -- Dances with heads : parasitic mimesis and the government of savagery in colonial East Timor / Ricardo Roque -- Variants of frontier mimesis : colonial encounter and intercultural interaction in the Lao-Vietnamese uplands / Oliver Tappe -- The hut-hospital as project and as practice : mimeses, alterities, and colonial hierarchies / Cristiana Bastos -- Imitations of Buddhist statecraft : the patronage of Lao Buddhism and the reconstruction of relic shrines and temples in colonial French Indochina / Patrice Ladwig -- Colonial mimesis and animal breeding : Karakul sheep in southwestern Angola / Tiago Saraiva -- The colonial state and carnival : the complexity and ambiguity of carnival in Guinea-Bissau, West Africa / Christoph Kohl -- Conclusion: Notes on the conceptual history of mimesis / Patrice Ladwig.